Natural dyes: thickening madder, weld, and woad for screenprinting of Turkish inspired textile prints - Kritis, Matt (Kansas State University, 2010)
The overarching goals of the project were to acknowledge both traditional and modern aspects of Turkish culture, inform designers and researchers of natural dye and screen printing methods, and advance the developing practices of sustainable design. Mixed methodologies of scientific and practice-based research guided the project. A collection of 25 prints inspired by the Anatolian region of Turkey were screen-printed with thickened natural dyes onto sustainable fibered fabrics. The research of traditional Turkish art and culture led to the inspirational concepts and brought the textile prints to fruition. Understanding the dyeing practices, regional traditions, and political rule of this nation informed the design process and directly influenced the composition and imagery of the designs. The final outcomes were exhibited at the Kansas State University student union art gallery. Research was conducted on the use of natural plant-based dyes madder, weld, and woad for screen-printing by determining the most effective thickener and thickening method. Thickening agents gum tragacanth and gum arabic were tested for fabric hand and the printed natural dyes were tested for colorfastness to light. Gum tragacanth at a ratio of .9875 g agent to 10 ml water emerged as the most smooth and pliable when evaluating fabric hand. Colorfastness to light was as expected for madder and woad with excellent to good fastness. Weld had an unexpectedly low rating indicating further study is needed. The developing practices of sustainable design were advanced as I used sustainable materials (natural dyes, natural gums, naturally fibered fabrics) and methods (hand screenprinting) throughout the project. The information from this project may be valuable to artisans to further develop their natural dye and screen-printing techniques; to researchers to provide a foundation for testing additional thickened dyes; and to industry professionals to modify their practices.
Keywords: Natural dyes; Textiles; Screen-printing; Colorfastness; Sustainability; Design and Decorative Arts (0389); Fine Arts (0357)